Light transmission through intraocular lenses with or without yellow chromophore (blue light filter) and its potential influence on functional vision in everyday environmental conditions. Issue 1 (2nd January 2016) - Owczarek, Grzegorz; Gralewicz, Grzegorz; Skuza, Natalia; Jurowski, Piotr
Abstract : In this research the factors used to evaluate the light transmission through two types of acrylic hydrophobic intraocular lenses, one that contained yellow chromophore that blocks blue light transmission and the other which did not contain that filter, were defined according to various light condition, e.g., daylight and at night. The potential influence of light transmission trough intraocular lenses with or without yellow chromophore on functional vision in everyday environmental conditions was analysed.